2011
DOI: 10.4103/1596-3519.82078
|View full text |Cite
|
Sign up to set email alerts
|

Survey of medical specialists on their attitudes to and resources for health research in Nigeria

Abstract: Our study respondents regarded research highly but were severely constrained in conducting research by lack of access to sources of funding from within and outside Nigeria and finding time from core hospital functions. We recommend periodic (re)training in research particularly on how to apply for research grants and giving some protected research time for Nigerian medical specialists in order to boost their research function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 13 publications
2
20
0
Order By: Relevance
“…Research funding was one of the main barriers to conducting research. This is consistent with the findings from Nigeria amongst the ophthalmologists [ 7 ] and medical specialists [ 8 ] and East African orthopedic surgeons [ 6 ]. Personal funds were the main source of funding for Nigerian ophthalmologists and medical specialist.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Research funding was one of the main barriers to conducting research. This is consistent with the findings from Nigeria amongst the ophthalmologists [ 7 ] and medical specialists [ 8 ] and East African orthopedic surgeons [ 6 ]. Personal funds were the main source of funding for Nigerian ophthalmologists and medical specialist.…”
Section: Discussionsupporting
confidence: 92%
“…Perhaps, there is also an element of altruism as well. Enhancement of knowledge was also the greatest incentive for conducting research amongst the Nigerian ophthalmologist [ 7 ] and medical specialists [ 8 ], East African orthopedic surgeons [ 6 ] and Asian doctors [ 10 ]. However, financial gains and fame featured quite prominently in the Nigerian and Asian studies.…”
Section: Discussionmentioning
confidence: 99%
“…Research funding was one of the main barriers for conducting research. This is consistent with the findings from Nigeria amongst the ophthalmologists (7) and medical specialists (8) and East African orthopedic surgeons (6). Personal funds was the main source of funding for Nigerian ophthalmologists and medical specialist.…”
Section: Discussionsupporting
confidence: 91%
“…At the tertiary level of care, the tripod of clinical duties includes service, teaching and research. A previous study conducted among medical specialists in Nigeria 4 showed that research function was ranked third by 64.7% of the participants in that study, behind service and training. A similar study revealed that the spectrum of research tilted more towards low-budget crosssectional surveys and retrospective studies due to the challenges of lack of funds, work overload, time constraints and insufficient infrastructural supports.…”
Section: Introductionmentioning
confidence: 75%